Juridical Review of the Issuance of Police Clearance Certificates (SKCK) Using National Health Insurance (JKN) Based on Police Regulation Number 6 of 2023 - Ni Putu Nadya Guna Artha Prasasta; Erikson Sihotang; Anak Agung Gde Putra Arjawa (Journal Of Social Science (JoSS), 2025)
The application of the National Health Insurance (JKN) membership requirement in the process of issuing a Certificate of Good Conduct (SKCK) has resulted in various problems, especially for those who are not registered as members. The purpose of this study was to evaluate the impact of the JKN membership requirement in the SKCK issuance process and identify the obstacles faced by the community. This study used a normative research method with legal analysis based on applicable regulations. The data used includes primary and secondary legal materials. The results showed that the regulation requiring JKN membership is contrary to the applicable law, namely Law Number 25 of 2009 concerning Public Services. This requirement creates obstacles in accessing public services that should be inclusive. This study examines the various challenges faced by the community in meeting these requirements and assesses their compliance with the principles of good public service. Policies that require JKN membership as a condition for issuing a Certificate of Good Conduct (SKCK) should be reviewed because they create barriers to accessing public services. Recommendations are made to remove these requirements in order to improve the inclusiveness and efficiency of public services.